Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Komitmen Organisasi Karyawan PT. Vale Tbk di Sorowako - Enjel Baru; Chalid Imran Musa; Tenri S.P. Dipoatmodjo; Muh. Ichwan Musa; Muh. Ikhwan Maulana Haeruddin (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of work environment and compensation on employee organizational commitment at PT. Vale Tbk in Sorowako. This type of research is quantitative research. The number of samples in this study were 60 employees who were employees in the Maintenance Department of PT. Vale. The data used are primary data and secondary data. Data collection was carried out using questionnaires and documentation. Data analysis techniques used in this study are validity and reliability tests, multiple regression analysis, classical assumption test, T test and F test. The results of the study after the data were processed with SPSS.23 showed that there was a positive influence between the variables Physical work environment (X1), Non-physical work environment (X2), Financial compensation (X3) and Non-financial compensation (X4) on Organizational Commitment variable (Y ) which can be shown through the results of the T test, namely the variable X1 has a t count of 3.970 > 2.004 (t table) and a sig. 0.000 < 0.05. Variable X2 has a t count of 3.254 > 2.004 (t table) and a sig. 0.002 <0.05. Variable X3 has a t count of 4.653 > 2.004 (t table) and a sig. 0.000 < 0.05. Variable X4 has a t count of 3.392 > 2.004 (t table) and a sig. 0.000 < 0.05.